Evaluation of a New Simplified Approach for Upper Superficial Impacted Third Molar Extraction-A Retrospective Split-Mouth Study - Alberto Materni; Karol Alí Apaza Alccayhuaman; Alberto Maltagliati; Daniele Botticelli; Stefano Benedicenti (MDPI AG, 2024)
Background: A new access technique was developed to reduce postoperative adverse events after the extraction of impacted maxillary wisdom teeth. Hence, this study aimed to assess the occurrence of adverse events after the extraction of maxillary impacted wisdom teeth using a traditional access (TA) or a new technique (NT). Methods: Two different surgical incision designs were used for bilateral wisdom tooth extractions in 30 patients. The traditional incision was performed distal to the second molar in the center of the tuberosity, followed by a buccal releasing incision. After the tooth extraction, the wound was secured by sutures. The new technique consists of an oblique incision from the distal palatal aspect of the tuberosity towards the buccal aspect of the second molar. After the tooth extraction, cyanoacrylate glue was used on the wound. Results: Lower pain was reported by patients at the site treated with the new technique (p < 0.01). Edema, postsurgical bleeding, and hematoma were similar in both groups. The surgical time was shorter for the new technique (p < 0.01). Conclusions: The new technique applied for the extraction of impacted maxillary wisdom teeth reduced postsurgical pain and the duration of surgery.